Project MIRACLE: Increasing empathy among psychosocial support staff working with refugees through brief training in motivational interviewing - Miriam Potocky; Kristen L Guskovict (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas, 2019)
Motivational interviewing (MI) is presented as a mental health and psychosocial support (MHPSS) approach for increasing empathy among psychosocial support staff working with refugees in resettlement. In a pilot study, 34 case managers in US refugee resettlement non-governmental organizations (NGOs) were trained in MI in a 3-h webinar format using a randomized controlled trial with a wait-list condition. Outcome was measured using the Helpful Responses to Refugees Questionnaire, which assesses empathetic responses to common refugee scenarios. Training group participants’ responses significantly improved from before to after training compared to the wait-list group which received no training; these results were subsequently replicated in the wait-list group after those participants received training. Pre–post effect sizes were medium to large. Participants reported that the training was useful and relevant, and that they applied the skills in their practice. Barriers and facilitators to use were reported. This pilot study had several limitations, including that the implementation of empathetic responses, their impact on the quality of the case manager–refugee relationship, and the ultimate impact on refugee outcomes could not be assessed. Implications for practice, NGO policy, future research and global MHPSS refugee programmes are discussed.